Determinants of response and resistance to CD19 chimeric antigen receptor (CAR) T cell therapy of chronic lymphocytic leukemia. (May 2018) - Fraietta, Joseph; Lacey, Simon; Orlando, Elena; Pruteanu-Malinici, Iulian; Gohil, Mercy; Lundh, Stefan; Boesteanu, Alina; Wang, Yan; O'Connor, Roddy; Hwang, Wei-Ting; Pequignot, Edward; Ambrose, David; et al.
Abstract Tolerance to self-antigens prevents the elimination of cancer by the immune system1, 2 . We used synthetic chimeric antigen receptors (CARs) to overcome immunological tolerance and mediate tumor rejection in patients with chronic lymphocytic leukemia (CLL). Remission was induced in a subset of subjects, but most did not respond. Comprehensive assessment of patient-derived CAR T cells to identify mechanisms of therapeutic success and failure has not been explored. We performed genomic, phenotypic and functional evaluations to identify determinants of response. Transcriptomic profiling revealed that CAR T cells from complete-responding patients with CLL were enriched in memory-related genes, including IL-6/STAT3 signatures, whereas T cells from nonresponders upregulated programs involved in effector differentiation, glycolysis, exhaustion and apoptosis. Sustained remission was associated with an elevated frequency of CD27+ CD45RO– CD8+ T cells before CAR T cell generation, and these lymphocytes possessed memory-like characteristics. Highly functional CAR T cells from patients produced STAT3-related cytokines, and serum IL-6 correlated with CAR T cell expansion. IL-6/STAT3 blockade diminished CAR T cell proliferation. Furthermore, a mechanistically relevant population of CD27+ PD-1– CD8+ CAR T cells expressing high levels of the IL-6 receptor predicts therapeutic response and is responsible for tumor control. These findings uncover new features of CAR T cell biology and underscore the potential of using pretreatment biomarkers of response to advance immunotherapies. An IL-6/STAT3 signature and memory CD8 T cell subset in preinfusion chimeric antigen receptor–expressing T cells associate with response in patients with high-risk chronic lymphocytic leukemia.